An Alternative Carbon Carrier in Green Preparation of Efficient Gold/Carbon Catalyst for Acetylene Hydrochlorination. Issue 14 (14th June 2019) - Lai, Huixia; Wang, Bolin; Yue, Yuxue; Sheng, Gangfeng; Wang, Saisai; Feng, Feng; Zhang, Qunfeng; Zhao, Jia; Li, Xiaonian
Abstract: Au catalysts supported with carbon‐based carriers have been extensively studied for the hydrochlorination of acetylene and expected to replace toxic mercury catalysts. However, removal of the highly corrosive aqua regia used in the preparation of carbon‐based catalysts while maintaining catalytic activity and stability remains a key challenge. Herein, we present a green technology carrier, activated carbon fibers (ACF), to support gold catalysts for the hydrochlorination of acetylene. TPD and XPS analyses confirmed the presence of surface oxygen‐containing functional groups (SOGs) and pyrrolic N species on the ACF. The Au/ACF−H2 O catalyst exhibited better catalytic activity and stability than Au/ROX0.8(AQ)−H2 O. Characterization results revealed that the catalytic properties of Au/ACF−H2 O could be attributed to the anchoring and stabilization of gold active species on the SOGs, leading to atomic dispersion, and to the improvement of HCl adsorption with the synergistic effect of electron‐donating pyrrolic N groups. The results indicated that usage of this green carrier can be considered as the a new approach to reduce or eliminate the use of strong oxidizing reagents in the preparation of Au catalysts. Abstract : Ready, steady, gold ! A new pathway was opened though the usage of green carrier to reduce/eliminate the use of strong oxidizing reagents in the preparation of Au catalysts for the hydrochlorination of acetylene.